SEMI-ORTHOGONAL PROPERTY OF A CLASS OF THE GAUSS’ HYPERGEOMETRIC POLYNOMIALS - Bajpai, S. D.; Arora, M. S. (Matematichki Bilten, 1993)
We establish a semi-orthogonal property for a class of Gauss’ hypergeometric polynomials with an elementary weight function and employ it to generate a theory concerning the finite series expansion involving the Gauss’ hypergeometric polynomials.